Promoter methylation and age-related downregulation of Klotho in rhesus monkey - King, Gwendalyn D. (Springer Netherlands, 2011)
While overall DNA methylation decreases with age, CpG-rich areas of the genome can become hypermethylated. Hypermethylation near transcription start sites typically decreases gene expression. Klotho (KL) is important in numerous age-associated pathways including insulin/IGF1 and Wnt signaling and naturally decreases with age in brain, heart, and liver across species. Brain tissues from young and old rhesus monkeys were used to determine whether epigenetic modification of the KL promoter underlies age-related decreases in mRNA and protein levels of KL. The KL promoter in genomic DNA from brain white matter did not show evidence of oxidation in vivo but did exhibit an increase in methylation with age. Further analysis identified individual CpG motifs across the region of interest with increased methylation in old animals. In vitro methyl modification of these individual cytosine residues confirmed that methylation of the promoter can decrease gene transcription. These results provide evidence that changes in KL gene expression with age may, at least in part, be the result of epigenetic changes to the 5′ regulatory region.